2023
DOI: 10.3390/children10030424
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Telerehabilitation-Based Structured Home Program on Activity, Participation and Goal Achievement in Preschool Children with Cerebral Palsy: A Triple-Blinded Randomized Controlled Trial

Abstract: A home program is implemented as an evidence-based mode of delivering services for physiotherapy and rehabilitation. Telerehabilitation is a method applied in physiotherapy modalities for children. This study aims to determine the effectiveness of usual care plus a Telerehabilitation-Based Structured Home Program on preschool children with cerebral palsy (CP) compared to usual care. Forty-three children aged 3–6 years (mean age 4.66 ± 1.08 years) with CP were randomly assigned to the Telerehabilitation-Based S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…Results of the present study showed that PT produce better gains when done more frequently. The GMFMER confirms that intensive PT yields better results, with an average GMFMER of 10.3 obtained for children treated 5 h per week or more (25,(33)(34)(35)(36)(37)(38). There is no doubt that SDR is very efficient in decreasing spasticity in children with CP ( 64) but the true effects on motor function were also difficult to interpret.…”
Section: Discussionmentioning
confidence: 69%
“…Results of the present study showed that PT produce better gains when done more frequently. The GMFMER confirms that intensive PT yields better results, with an average GMFMER of 10.3 obtained for children treated 5 h per week or more (25,(33)(34)(35)(36)(37)(38). There is no doubt that SDR is very efficient in decreasing spasticity in children with CP ( 64) but the true effects on motor function were also difficult to interpret.…”
Section: Discussionmentioning
confidence: 69%
“…The objectives of TR are to conduct a distance-therapeutic intervention programme, assess rehabilitative therapies and track their outcomes, and offer distance education and counselling. Research indicates that TR has potential applications in the eld of paediatric rehabilitation and physiotherapy [24]. Despite the possible advantages, not much research has been done on how the quality of life (QL) and FC symptoms in children who are constipated are affected by the telerehabilitation home program (TRP).…”
Section: Introductionmentioning
confidence: 99%